Information Society, Cultural Identity and Missions of Universities - Zahra Karimian; Ali Mohammad Ahmadvand (Taḥqīqāt-i Farhangī-i Īrān)
Based on Horizon perspective of twenty years: "Iran Is developed country with the first position in Economy, science & technology in the level of area, with Islamic Identity in world and constructive interaction & influence in the International relationship ... ". In the most important document of national development of Iran, has been emphasized on strengthening of Iran- Islam culture & needs to enjoy of Information technology & good international communication as an index of national power. Specially, fast hanging of Information technology in new ages caused to deep social- cultural influence in the today informative society in addition to knowledge & technology dimension of it. Emerge of new communication & information technology has provided possibility in appearing the area divergent identity & also it lead to world divergent in the field of culture & identity. In this way, universities has special position in achievement to the aims of development view because of having different role in fields of science, technology & culture in guidance & training of the most important human capital. Regard to this, we attempt to present the conceptual framework based on analytical study and some theories about cultural identity & information society and describe the tasks of universities about it.